DIFFERENCES OF STUDENT LEARNING OUTCOMES AND ABILITY TO DELIVER INFORMATION ON PICTURE AND PICTURE AND INSIDE OUTSIDE CIRCLE LEARNING MODEL ON VIRUSES - Sartika Romauli Sinaga; Hudson Sidabutar; Elita Aritonang (Jurnal Pelita Pendidikan, 2021)
This study aims to determine the differences in learning outcomes and convey information to students taught using the Picture and Picture and Inside-Outside Circle learning model on virus material in class X IPA SMA Negeri 2 Siborongborong. The sampling technique used was simple random sampling technique, with 32 students as the first experimental class (I) using the Picture and picture model, and 31 students as the second experimental class (II) using the Inside outside circle model. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis. The hypothesis testing results using the Independent Sample T-test showed that the student learning outcomes obtained the sig value. 0.029 <0.05, while the ability to convey student information obtained a sig value. 0.031 <0.05. The hypothesis testing results show differences in learning outcomes and students' ability to convey information using the Picture and Picture and Inside-Outside Circle learning model on virus material in class X IPA SMA Negeri 2 Siborongborong.